Association of Adrenal Venous Sampling With Outcomes in Primary Aldosteronism for Unilateral Adenomas - Thiesmeyer, Jessica W. (JAMA Surg, 2020)
IMPORTANCE: Adrenal venous sampling is recommended prior to adrenalectomy for all patients with hyperaldosteronism; however, cross-sectional imaging resolution continues to improve, while the procedure remains invasive and technically difficult. Therefore, certain patients may benefit from advancing straight to surgery. OBJECTIVE: To determine whether clinical and biochemical resolution varied for patients with primary aldosteronism with unilateral adenomas who underwent adrenal venous sampling vs those who proceeded to surgery based on imaging alone. DESIGN, SETTING, AND PARTICIPANTS: Retrospective, international cohort study of patients treated at 3 tertiary medical centers from 2004 to 2019, with a median follow-up of approximately 6 months. A total of 217 patients were consecutively enrolled. Exclusion criteria consisted of unknown postoperative serum aldosterone level and imaging inconsistent with unilateral adenoma with a normal contralateral gland. A total of 125 patients were included in the analysis. Data were analyzed between October 2019 and July 2020. EXPOSURES: Adrenal venous sampling performed preoperatively. MAIN OUTCOMES AND MEASURES: The primary outcome measurements were the clinical and biochemical success rates of surgery for the cure of hyperaldosteronism secondary to aldosterone-producing adenoma. RESULTS: A total of 125 patients were included (45 cross-sectional imaging with adrenal venous sampling and 80 imaging only). The mean (SD) age of the study participants was 50.2 (10.6) years and the cohort was 42.4% female (n = 53). Of those patients for whom race or ethnicity were reported (n = 80), most were White (72.5%). Adrenal venous sampling failure rate was 16.7%, and the imaging concordance rate was 100%. Relevant preoperative variables were similar between groups, except ambulatory systolic blood pressure, which was higher in the imaging-only group (150 mm Hg; interquartile range [IQR], 140-172 mm Hg vs 143 mm Hg, IQR, 130-158 mm Hg; P = .03). Resolution of autonomous aldosterone secretion was attained in 98.8% of imaging-only patients and 95.6% of adrenal venous sampling patients (P = .26). There was no difference in complete clinical success (43.6% [n = 34] vs 42.2% [n = 19]) or partial clinical success (47.4% [n = 37] vs 51.1% [n = 23]; P = .87) between groups. Complete biochemical resolution was similar as well (75.9% [n = 41] vs 84.4% [n = 27]; P = .35). There was no difference in clinical or biochemical cure rates when stratified by age, although complete clinical success rates downtrended in the older cohorts, and sample sizes were small. CONCLUSIONS AND RELEVANCE: Given the improved sensitivity of cross-sectional imaging in detection of adrenal tumors, adrenal venous sampling may be selectively performed in appropriate patients with clearly visualized unilateral adenomas without affecting outcomes. This may facilitate increased access to surgical cure for aldosterone-producing adenomas and will decrease the incidence of morbidities associated with the procedure.